2020
DOI: 10.1155/2020/8159628
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Fenton Oxidation Using Magnesium Ferrite Nanoparticles for Ibuprofen Removal from Wastewater: Optimization and Kinetics Studies

Abstract: In this study, the catalytic properties of Fenton-like catalyst based on magnesium ferrite nanoparticles for IBP degradation were examined. Structural and morphological studies showed the low crystallinity and mesoporous structure for the catalyst obtained via a glycine-nitrate method. The influences of catalyst dosage, oxidant concentration, and solution pH on the pollutant degradation were investigated. The pseudo-first-order model describes kinetic data, and under optimal condition (catalyst dose of 0.5 g L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 40 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…DFC is a NSAID engaged for inflammation treatment and most frequently administered for pain relief in humans and animals with expected usage escalations in the course of the Covid-19 pandemic [88] , [89] . IBU is a non-steroidal anti-inflammatory drug (NSAID), entrusted with pain and fever relief, arthritis, and to treat inflammation of minor injuries since its first introduction in 1969, being recently selected as the safest NSAID by spontaneous consumption which has surpassed 200 tons per year [90] .…”
Section: Z-scheme Photocatalysismentioning
confidence: 99%
“…DFC is a NSAID engaged for inflammation treatment and most frequently administered for pain relief in humans and animals with expected usage escalations in the course of the Covid-19 pandemic [88] , [89] . IBU is a non-steroidal anti-inflammatory drug (NSAID), entrusted with pain and fever relief, arthritis, and to treat inflammation of minor injuries since its first introduction in 1969, being recently selected as the safest NSAID by spontaneous consumption which has surpassed 200 tons per year [90] .…”
Section: Z-scheme Photocatalysismentioning
confidence: 99%
“…However, the concentrations of pharmaceuticals in water are usually very low, which make removal of them much difficult (Khan et al 2021a). Magnesium ferrite nanomaterials have been used to remove salicylic acid (a derivative of different medicine), minocycline (a tetracycline antibiotic) and ibuprofen from water through adsorption process (Lu et al 2016;Ivanets et al 2020;Tatarchuk et al 2020b).…”
Section: Removal Of Radioactives and Other Contaminantsmentioning
confidence: 99%
“…It is reported that there are many ways to effectively activate persulfate (peroxymonosulfate/peroxydisulfate), heat (Hu et al 2019), ultrasound (Kermani et al 2020), transition ions (Guo et al 2020), ultraviolet radiation (Hsieh et al 2021), electrolysis-activated (Wang et al 2021), but as a homogeneous activation system these methods require more energy consumption. It is found that magnesium ferrite lack of the above mentioned disadvantage and had enhanced catalytic performance for pharmaceutical products and organic dyes mineralization (Ivanets et al 2020(Ivanets et al , 2021. Bimetallic and trimetallic iron-based systems belonging to the family of spinel with the molecular structure of MFe 2 O 4 (M can be Ni, Zn, Mn, Cu, etc.)…”
Section: Introductionmentioning
confidence: 99%